Causes behind of Gender Based Violence: An Empirical Study on Internally-Displaced People from Mosul - Ali Zedan Ahmed; Zana Ahmad Perdawd; Sabah Ahmed Mohamed Najar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Violence in general and gender-based violence in particular are topics of much interest and concern today especially because they pose a threat to social cohesion and other aspects of the public life. Studying violence by default includes investigating the society as a whole including culture, language, and tradition. Violence based on gender attempts to assign roles to individuals in society based on their social gender. As a result, many societies have been dominated by a patriarchic system where males have benefited and females have been victimized. In abnormal circumstances such as at times of war, displacement and political unrest, gender-based violence seems to be especially commonly practiced amongst displaced people and refugees, primarily because this type of violence is deep rooted in culture, regardless of status or location. When the political system is at risk, people tend to adhere to their social traditions perhaps as a protective measure. The behavioral consequences of old traditions and dogmatic thinking are evident in different types of acts of violence such as forced marriage, underage marriage, punitive beating and denial of access to education and health care. These acts are practiced commonly and have been accepted as normal behaviors as a result of their long-standing tradition in the social and perhaps religious establishment. They have been internalized and accepted as norms. Consequently, their execution does not bring about feelings of guilt or wrongdoing. Therefore, although acts of violence are dominant, little reaction is generated from society and public institutions. The main implications of the presence of this type of violence and its behavioral manifestations are that the perpetrators present their acts as legitimate and themselves as guardians of social norms and even sacred religious values. As such, they represent a social authority protecting social and religious systems and public interest. They therefore do not shy away to interfere in people’s most private matters such as female genital mutilation and relationships. They altogether might lead to social disintegration, injustice, deprivation and inability affecting all layers of society. Once practiced over a lengthy period of time and established as accepted norms, gender-based violence poses a serious threat on social cohesion and family structure exacerbated by displacement and war. Families and individuals who experience gender-based violence might be more susceptible to practice them on others. This study investigates gender-based violence from a theoretical and practical perspective and using a sociological stance to identify the types of gender-based violence, its relation to the social system and cohesion. The study involves participants from two internally-displaced camps in Khazer M1 and Hasan Sham U2. The data were collected through interviews with displaced people from Mosul in these two camps.